ANALISIS DAN PEMBERDAYAAN RUMAH TANGGA MISKIN DI KECAMATAN GUNUANG OMEH KABUPATEN LIMA PULUH KOTA - Zil Makmur; Hasdi Aimon; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze poor households in Gunuang Omeh Subdistrict, Lima Puluh Kota Districts, namely: Family Education (X1), Family Health (X2), Work Ethics (X3). The type of data in this study is primary data. Analysis of the data used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: Logistic Regression Model, Likelihood Ratio Test and Wald Test. The results showed that (1) Family education had a positive and significant effect on household poverty in Gunuang Omeh Subdistrict, Lima Puluh Kota Districts. (2) Family health does not have a significant effect on household poverty in Gunuang Omeh Subdistrict, Lima Puluh Kota Districts. (3) Work ethic has a significant effect on household poverty in Gunuang Omeh Subdistrict, Lima Puluh Kota Districts. (4) Together there is a significant influence between family education, family health and work ethic on household poverty in Gunuang Omeh Subdistrict Lima Puluh Kota Districts.